Qualitative self-coding as reflection: empowering teacher candidates with the tools of the researcher. Issue 3 (3rd May 2020) - Valtierra, Kristina M.; Siegel, Lesley N.
ABSTRACT: Reflective journaling is common practice in teacher preparation and often utilized as a tool to cultivate teacher candidates' dispositional development. This paper details a study that implemented a methodology of teaching self-coding to 45 preservice teacher candidates as a pedagogical tool to support reflective practices within a field-based course. Analysis of teacher candidates' codes and written reflections on the process suggest that the authors' self-coding method helped teacher candidates develop concrete understandings of the relationship between professional teaching dispositions and pedagogical decision-making. Further, findings suggest that two cycles of self-coding facilitated a continuum of reflection wherein teacher candidates initially gained tangible awareness about professional teaching dispositions, and over time translated their new understandings to deeper analysis of their reflections, which elicited asset-based views of diverse learners. Findings suggest that by sharing the tools of a researcher, teacher educators can enhance candidates' reflective capacities, which in turn can support dispositional growth, deeper reflection and reflexivity.